Modern and Belligerent: Entertainment and Pedagogy in "Galicia Emigrante’s" Literary Feuilleton - García Martínez, Pablo (Madrygal. Revista de Estudios Gallegos, 2020)
This article uses as its conducting thread the narrative literature published by the literary feuilleton included in the magazine Galicia Emigrante (1954-1959, 37 números), edited by the republican exile Luís Seoane. The text connects the short stories published by the magazine to the efforts for popular education articulated in Galicia Emigrante. At the same time, the text relates this project to those transatlantic Cultural Cold Wars that were refracted, especially during the nineteen-fifties, to the culture organic to Galicianism. Using this framework, the article analyzes the narrative litera-ture published in Galicia Emigrante’s literary feuilleton by Antonio Baltar, Eduardo Blanco- Amor, Xosé Neira Vilas, Leopoldo Nóvoa, Xosé Núñez Búa, Xosé Ruibal, and Ramón de Valenzuela. The article’s interest arises, first, from its analysis of narrations that set a precedent for milestones in post-war Galician literature –namely, Non agardei por ninguén (1957) and A Esmorga (1959). Moreover, the text engages with Galician intellectual history from the same period, since it makes visible the project of a third way articulated by the Galicia Emigrante intellectuals, who tried to unsuccessfully affect the debates on the future of a Galician nationalism resisting Francoism, either on exile or, if in Galicia, underground.
Keywords: Galicia Emigrante (Magazine); Literature and Pedagogy; Cultural Cold Wars; Print Culture